Gadolinia particles and method for producing gadolinia particles

By heat treatment of praseodymium lithium compounds with technetium compounds, lanthanum lithium particles containing technetium were prepared, which solved the problem that the existing methods failed to directly synthesize high-performance lithium particles, and achieved improvement in particle performance and enhancement of application value.

JP7677464B2Active Publication Date: 2025-05-15DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023575707
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2025-05-15
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

The existing manufacturing methods do not directly synthesize high-performance lanthanum lithium particles from raw materials, resulting in limitations on the research and application of lanthanum lithium particles and their manufacturing methods.

Method used

By heat treatment of the praseodymium lithium compound with the technetium compound, lanthanum lithium particles containing technetium are prepared, and by adjusting the type and content of the technetium compound, the size and surface distribution of the particles are controlled, thereby improving its performance.

Benefits of technology

It has achieved the preparation of lanthanum lithium particles with excellent performance, including good catalytic activity and self-forming characteristics, and the application value of the product is improved by optimizing process conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007677464000002
    Figure 0007677464000002
  • Figure 0007677464000003
    Figure 0007677464000003
  • Figure 0007677464000004
    Figure 0007677464000004
Patent Text Reader

Abstract

Gadolinia particles containing molybdenum. A method for producing said gadolinia particles, comprising calcining a gadolinium compound in the presence of a molybdenum compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to gadolinia particles and a method for producing gadolinia particles. [Background technology]

[0002] Gadolinium oxide (i.e., gadolinia) is being used and researched for a wide range of applications, including optical applications such as phosphor host materials, optical glasses, optical isolator substrates, laser elements, and photonic crystals, as well as memory materials.

[0003] For example, Patent Document 1 discloses that gadolinia-doped ceria (GDC) / gadolinia (Gd2O3) granules were produced using gadolinia-doped ceria (GDC) powder and gadolinia (Gd2O3) powder. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2014-511260 Summary of the Invention [Problem to be solved by the invention]

[0005] However, Patent Document 1 discloses a method for producing the above-mentioned granules, but does not disclose a method for producing gadolinia particles by synthesizing the gadolinia particles themselves from a raw material. Thus, knowledge about gadolinia particles and methods for producing them is limited, and there is still room for further study.

[0006] Therefore, an object of the present invention is to provide gadolinia particles having excellent properties and a method for producing said gadolinia particles. [Means for solving the problem]

[0007] The present invention includes the following aspects.

[0008] (1) Gadolinia particles containing molybdenum. (2) The median diameter D of the gadolinia particles calculated by a laser diffraction / scattering method 50 The gadolinia particles according to (1) above, having a diameter of 0.1 to 1000 μm. (3) Gadolinia particles according to (1) or (2), wherein a Gd2O3 content (G1) relative to 100 mass% of the gadolinia particles as determined by XRF analysis of the gadolinia particles is 60 to 99.95 mass%, and a MoO3 content (M1) relative to 100 mass% of the gadolinia particles as determined by XRF analysis of the gadolinia particles is 0.05 to 40 mass%. (4) Gadolinia particles according to any one of (1) to (3), wherein a Gd2O3 content (G2) relative to 100 mass% of the surface layer of the gadolinia particle, as determined by XPS surface analysis of the gadolinia particle, is 10 to 98 mass%, and a MoO3 content (M2) relative to 100 mass% of the surface layer of the gadolinia particle, as determined by XPS surface analysis of the gadolinia particle, is 2 to 40 mass%. (5) A method for producing gadolinia particles according to any one of (1) to (4), comprising the steps of: A method for producing gadolinia particles comprising calcining a gadolinium compound in the presence of a molybdenum compound. (6) The method for producing gadolinia particles according to (5) above, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate and sodium molybdate. (7) The method for producing gadolinia particles according to (5) or (6) above, wherein the sintering temperature is 900 to 1600° C. Effect of the Invention

[0009] According to the present invention, it is possible to provide gadolinia particles having excellent properties and a method for producing said gadolinia particles. [Brief description of the drawings]

[0010] [Figure 1] 1 is a SEM photograph of gadolinia particles of Example 1. [Diagram 2] 1 is a SEM photograph of gadolinia particles of Example 2. [Diagram 3] 1 is a SEM photograph of gadolinia particles of Example 3. [Figure 4] 1 is a SEM photograph of gadolinia particles of Example 4. [Diagram 5] 1 is a SEM photograph of gadolinia particles of Comparative Example 1. [Figure 6] 1 is a SEM photograph of gadolinia particles of Comparative Example 2. [Figure 7] 1 is a graph showing the results of XRD measurement of gadolinia particles of an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the gadolinia particles and the method for producing gadolinia particles of the present invention will be described.

[0012] <Gadolinia particle> The gadolinia particles of the embodiment contain molybdenum. The gadolinia particles of the embodiment contain molybdenum and have excellent properties such as catalytic activity and shape derived from molybdenum.

[0013] The gadolinia particles of one embodiment produced by the production method of the embodiment can have a specific idiomorphic shape such as a granular or columnar shape, as will be shown in the examples described later.

[0014] In this specification, the term "columnar" includes prismatic, cylindrical, rod-like, etc. The shape of the bottom surface of the columnar body of the columnar gadolinia particle is not particularly limited, and examples thereof include circular, elliptical, polygonal, etc. The columnar body also includes a shape that extends straight in the length direction, extends at an angle, extends while curving, extends branch-like, etc.

[0015] In the manufacturing method of the gadolinia particles according to the embodiment, the particle size, degree of aggregation, molybdenum content, etc. of the obtained gadolinia particles can be controlled by controlling the amount and type of the molybdenum compound used in the manufacturing method described below.

[0016] The median diameter D of the gadolinia particles of the embodiment calculated by a laser diffraction / scattering method 50 The thickness is preferably 0.1 to 1000 μm, more preferably 3 to 100 μm, and further preferably 5 to 20 μm.

[0017] From the viewpoint of providing gadolinia particles having a larger size, the median diameter D of the gadolinia particles of the embodiment calculated by a laser diffraction / scattering method is 50 The thickness is preferably from 25 to 200 μm, more preferably from 30 to 100 μm, and further preferably from 40 to 80 μm.

[0018] The median diameter D of the gadolinia particle sample calculated by the laser diffraction / scattering method 50 can be calculated as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0019] The particle diameter D of the gadolinia particle of the embodiment calculated by a laser diffraction scattering method 10 The thickness is preferably 0.05 to 100 μm, more preferably 0.08 to 50 μm, and further preferably 0.1 to 5 μm.

[0020] From the viewpoint of providing gadolinia particles having a larger size, the particle diameter D of the gadolinia particles of the embodiment calculated by a laser diffraction / scattering method is 10 The thickness is preferably 6 to 80 μm, more preferably 8 to 50 μm, and further preferably 10 to 30 μm.

[0021] The particle diameter D of the gadolinia particle sample calculated by the laser diffraction and scattering method 10can be calculated as the particle size at which the volume cumulative percentage of small particles is 10% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0022] The particle diameter D of the gadolinia particle of the embodiment calculated by a laser diffraction scattering method 90 The thickness is preferably from 1 to 1500 μm, more preferably from 2 to 500 μm, and further preferably from 8 to 50 μm.

[0023] From the viewpoint of providing gadolinia particles having a larger size, the particle diameter D of the gadolinia particles of the embodiment calculated by a laser diffraction / scattering method is 90 The thickness is preferably 60 to 800 μm, more preferably 80 to 500 μm, and further preferably 100 to 200 μm.

[0024] The particle diameter D of the gadolinia particle sample calculated by the laser diffraction and scattering method 90 can be calculated as the particle size at which the volume cumulative percentage of small particles is 90% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0025] The gadolinia particles of the embodiment include gadolinium oxide (i.e., gadolinia). Examples of gadolinium oxide that may be included in the gadolinia particles of the embodiment include Gd2O3 and GdO2.

[0026] The gadolinia particles of the embodiment preferably contain 60 to 99.95 mass % of Gd2O3, more preferably 65 to 99.5 mass %, and even more preferably 80 to 98 mass %, relative to 100 mass % of the gadolinia particles.

[0027] The gadolinia content in the gadolinia particles can be measured by XRF analysis. In the gadolinia particles of the embodiment, the Gd2O3 content (G1) relative to 100 mass% of the gadolinia particles, determined by XRF analysis of the gadolinia particles, is preferably 60 to 99.95 mass%, more preferably 65 to 99.5 mass%, and even more preferably 70 to 98 mass%.

[0028] The gadolinia particles of the embodiment contain molybdenum. The gadolinia particles of the embodiment preferably have an MoO3 content (M1) of 0.05 to 40 mass%, more preferably 0.1 to 35 mass%, and even more preferably 1 to 30 mass%, relative to 100 mass% of the gadolinia particles, determined by XRF analysis of the gadolinia particles.

[0029] In the gadolinia particles of the embodiment, the upper and lower limit values ​​of the Gd2O3 content (G1) and the MoO3 content (M1) exemplified above can be freely combined. In addition, the values ​​of the Gd2O3 content (G1) and the MoO3 content (M1) can also be freely combined.

[0030] An example of the gadolinia particles of the embodiment is gadolinia particles having a Gd2O3 content (G1) of 60 to 99.95 mass % and a MoO3 content (M1) of 0.05 to 40 mass %.

[0031] The Gd2O3 content (G1) and the MoO3 content (M1) can be measured by XRF analysis using, for example, an X-ray fluorescence analyzer (Primus IV) manufactured by Rigaku Corporation.

[0032] The gadolinia content in the surface layer of the gadolinia particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. In the gadolinia particle of the embodiment, the Gd2O3 content (G2) relative to 100 mass% of the surface layer of the gadolinia particle, as determined by XPS surface analysis of the gadolinia particle, is preferably 10 to 98 mass%, more preferably 20 to 80 mass%, and even more preferably 30 to 65 mass%.

[0033] The gadolinia particles of this embodiment preferably have an MoO3 content (M2) of 2 to 40 mass%, more preferably 3 to 35 mass%, and even more preferably 8 to 30 mass%, relative to 100 mass% of the surface layer of the gadolinia particles, as determined by XPS surface analysis of the gadolinia particles.

[0034] In the gadolinia particles of the embodiment, the upper and lower limit values ​​of the Gd2O3 content (G2) and the MoO3 content (M2) exemplified above can be freely combined. In addition, the values ​​of the Gd2O3 content (G2) and the MoO3 content (M2) can also be freely combined.

[0035] An example of the gadolinia particles of the embodiment is gadolinia particles having the Gd2O3 content (G2) of 10 to 98 mass % and the MoO3 content (M2) of 2 to 40 mass %.

[0036] The above Gd2O3 content (G2) refers to the value obtained by performing XPS surface analysis of a gadolinia particle sample using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the gadolinium content into its oxide content, and calculating the Gd2O3 content relative to 100% by mass of the surface layer of the gadolinia particle.

[0037] The MoO3 content (M2) mentioned above refers to the value obtained by performing XPS surface analysis of the gadolinia particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the molybdenum content into an oxide, and calculating the MoO3 content relative to 100% by mass of the surface layer of the gadolinia particles.

[0038] In the gadolinia particle of the embodiment, the molybdenum is preferably unevenly distributed in the surface layer of the gadolinia particle.

[0039] Here, in this specification, the term "surface layer" refers to a region within 10 nm from the surface of the gadolinia particle of the embodiment. This distance corresponds to the detection depth of the XPS used for measurement in the examples.

[0040] Here, "distributed unevenly in the surface layer" refers to a state in which the mass of molybdenum or molybdenum compounds per unit volume in the surface layer is greater than the mass of molybdenum or molybdenum compounds per unit volume in areas other than the surface layer.

[0041] In the gadolinia particles of this embodiment, the fact that molybdenum is concentrated in the surface layer of the gadolinia particles can be confirmed by the fact that the MoO3 content (M2) relative to 100% by mass of the surface layer of the gadolinia particles, determined by XPS surface analysis of the gadolinia particles, is greater than the MoO3 content (M1) relative to 100% by mass of the gadolinia particles, determined by XRF (X-ray fluorescence) analysis of the gadolinia particles, as shown in the examples described later.

[0042] In the gadolinia particles of the embodiment, as an indicator that molybdenum is unevenly distributed in the surface layer of the gadolinia particles, the gadolinia particles of the embodiment preferably have a surface layer uneven distribution ratio (M2 / M1) of the MoO3 content (M2) to the MoO3 content (M1) of more than 1 and not more than 20, more preferably 1.1 to 10, and even more preferably 1.5 to 5.

[0043] By distributing molybdenum or a molybdenum compound unevenly in the surface layer, excellent properties such as catalytic activity can be imparted more efficiently than when molybdenum or a molybdenum compound is present not only in the surface layer but also uniformly in the area other than the surface layer (inner layer).

[0044] The gadolinia particles of this embodiment may further contain lithium, potassium, or sodium in addition to molybdenum.

[0045] <Method of manufacturing gadolinia particles> The method for producing gadolinia particles according to the embodiment includes calcining a gadolinium compound in the presence of a molybdenum compound. More specifically, the method for producing gadolinia particles according to the embodiment may include mixing a gadolinium compound and a molybdenum compound to form a mixture, and calcining the mixture.

[0046] According to the method for producing gadolinia particles of the embodiment, it is possible to produce the gadolinia particles of the embodiment described above.

[0047] A preferred method for producing gadolinia particles includes a step of mixing a gadolinium compound and a molybdenum compound to form a mixture (mixing step), and a step of firing the mixture (firing step).

[0048] [Mixing process] The mixing step is a step of mixing a gadolinium compound and a molybdenum compound to obtain a mixture. The contents of the mixture will be described below.

[0049] (Gadolinium Compounds) The gadolinium compound is not limited as long as it is a compound that can be turned into gadolinium oxide (i.e., gadolinia) by firing. Examples of the gadolinium compound include gadolinium oxide, gadolinium hydroxide, gadolinium carbonate, gadolinium chloride, and gadolinium nitrate, and gadolinium oxide is preferred.

[0050] The shape of the gadolinia particles after firing hardly reflects the shape of the raw material gadolinium compound, so any gadolinium compound can be suitably used, for example, in the form of a sphere, an amorphous structure with an aspect (wire, fiber, ribbon, tube, etc.), a sheet, etc.

[0051] (Molybdenum Compounds) The molybdenum compound includes molybdenum oxide, molybdate compounds, and the like.

[0052] The molybdenum oxide includes molybdenum dioxide, molybdenum trioxide, etc., and is preferably molybdenum trioxide.

[0053] The molybdate compound is MoO4 2- , Mo2O7 2- , Mo3O 10 2- , Mo4O 13 2- , Mo5O 16 2- , Mo6O 19 2- , Mo7O 24 6- , Mo8O 26 4- The molybdenum oxoanion may be, but is not limited to, a salt compound of the molybdenum oxoanion such as those mentioned above. The molybdenum oxoanion may be an alkali metal salt, an alkaline earth metal salt, or an ammonium salt.

[0054] The molybdate compound is preferably an alkali metal salt of a molybdenum oxoanion, more preferably lithium molybdate, potassium molybdate or sodium molybdate, and even more preferably potassium molybdate or sodium molybdate.

[0055] In the method for producing gadolinia particles of this embodiment, the molybdate compound may be a hydrate.

[0056] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, and more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate.

[0057] The method for producing gadolinia particles according to the embodiment may include a step of calcining a gadolinium compound in the presence of a molybdenum compound and a potassium compound.

[0058] The method for producing gadolinia particles according to the embodiment may include a step (mixing step) of mixing a gadolinium compound, a molybdenum compound, and a potassium compound to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0059] The method for producing gadolinia particles according to the embodiment may include a step (mixing step) of mixing a gadolinium compound and a compound containing molybdenum and potassium to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0060] A compound containing molybdenum and potassium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a potassium compound as fluxing agents and the use of a compound containing molybdenum and potassium as fluxing agents are both considered to be the use of a molybdenum compound and a potassium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a potassium compound.

[0061] The method for producing gadolinia particles according to the embodiment may include a step of calcining a gadolinium compound in the presence of a molybdenum compound and a sodium compound.

[0062] The method for producing gadolinia particles according to the embodiment may include a step (mixing step) of mixing a gadolinium compound, a molybdenum compound, and a sodium compound to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0063] Alternatively, the method for producing gadolinia particles of the embodiment may include a step (mixing step) of mixing a gadolinium compound and a compound containing molybdenum and sodium to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0064] A compound containing molybdenum and sodium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a sodium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a sodium compound as fluxing agents and the use of a compound containing molybdenum and sodium as fluxing agents are both considered to be the use of a molybdenum compound and a sodium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a sodium compound.

[0065] By firing a gadolinium compound in the presence of a molybdenum compound and a potassium compound, or in the presence of a molybdenum compound and a sodium compound, it is easy to adjust the particle size of the gadolinia particles produced, and for example, gadolinia particles with a large particle size can be easily produced. The reason for this is not clear, but the following reasons are thought to be possible. For example, K2MoO4 and Na2MoO4 are stable compounds and are difficult to volatilize during the firing process, so they are unlikely to undergo rapid reactions during the volatilization process, making it easy to control the growth of gadolinia particles. It is also thought that molten K2MoO4 and Na2MoO4 function like a solvent, allowing the particle size to be increased.

[0066] In the manufacturing method of gadolinia particles of this embodiment, a molybdenum compound is used as a fluxing agent. In the present specification, this manufacturing method using a molybdenum compound as a fluxing agent may be simply referred to as a "flux method". It is considered that, after the molybdenum compound reacts with the gadolinium compound at high temperature by the firing to form gadolinium molybdate, the gadolinium molybdate is further decomposed into gadolinium and molybdenum oxide at a higher temperature, the molybdenum compound is taken into the gadolinia particles. The molybdenum oxide is sublimated and removed from the system, and during this process, the molybdenum compound reacts with the gadolinium compound to form a molybdenum compound on the surface layer of the gadolinia particles. Regarding the mechanism of formation of the molybdenum compounds contained in the gadolinia particles, more specifically, it is believed that Mo-O-Gd is formed on the surface layer of the gadolinia particles by a reaction between molybdenum and Gd atoms, and when sintered at high temperatures, Mo is released and molybdenum oxide or compounds having Mo-O-Gd bonds are formed on the surface layer of the gadolinia particles.

[0067] Molybdenum oxide that is not incorporated into the gadolinia particles can be recovered and reused by sublimation, which reduces the amount of molybdenum oxide that adheres to the surfaces of the gadolinia particles and maximizes the inherent properties of the gadolinia particles.

[0068] On the other hand, the alkali metal salt of the molybdenum oxoanion does not vaporize even at the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also allows for a significant reduction in production costs.

[0069] In the above flux method, for example, when a molybdenum compound and a potassium compound are used in combination, it is believed that the molybdenum compound and the potassium compound react to form potassium molybdate. At the same time, the molybdenum compound reacts with a gadolinium compound to form gadolinium molybdate. Then, for example, gadolinium molybdate decomposes in the presence of liquid potassium molybdate, causing crystal growth, and it is believed that gadolinia particles with a large particle size can be easily obtained while suppressing the evaporation of the above flux (sublimation of MoO3).

[0070] The above mechanism is similar when a molybdenum compound and a potassium compound are used in combination (for example, when a compound containing molybdenum and sodium is used), and it is believed that gadolinium molybdate decomposes in the presence of liquid-phase sodium molybdate, causing crystal growth, making it possible to easily obtain gadolinia particles with a large particle size and a high molybdenum content.

[0071] (metal compound) The metal compound may be used during firing if desired. The method for producing gadolinia particles according to the embodiment may include, prior to the firing step, a step of mixing a gadolinium compound, a molybdenum compound, a potassium compound, and a metal compound to form a mixture (mixing step), and a step of firing the mixture (firing step).

[0072] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.

[0073] Examples of the Group II metal compound include magnesium compounds, calcium compounds, strontium compounds, and barium compounds.

[0074] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.

[0075] The above-mentioned metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the metal compounds are preferably oxides of metal elements. These metal compounds include isomers.

[0076] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use magnesium compounds, calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use magnesium compounds, calcium compounds, and yttrium compounds, and it is particularly preferred to use yttrium compounds.

[0077] The metal compound is preferably used in a proportion of, for example, 0 to 1.2 mass % (for example, 0 to 1 mol %) relative to the total amount of the gadolinium compounds used in the mixing step.

[0078] In the method for producing gadolinia particles of this embodiment, the amounts of the gadolinium compound and the molybdenum compound are not particularly limited, but preferably, 35% by mass or more of the gadolinium compound and 65% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired. More preferably, 40% by mass or more and 99% by mass or less of the gadolinium compound and 0.5% by mass or more and 60% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired. Even more preferably, 40% by mass or more and 90% by mass or less of the gadolinium compound and 10% by mass or more and 60% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired.

[0079] In the method for producing gadolinia particles according to the embodiment, the molar ratio (molybdenum / gadolinium) of the molybdenum atom in the molybdenum compound to the gadolinium atom in the gadolinium compound is preferably 0.01 or more, more preferably 0.03 or more, and even more preferably 0.1 or more. From the viewpoint of obtaining larger gadolinia particles, the molybdenum / gadolinium value is preferably 0.5 or more.

[0080] The upper limit of the molar ratio of molybdenum atoms in the molybdenum compound to gadolinium atoms in the gadolinium compound may be determined as appropriate, but from the viewpoint of reducing the amount of molybdenum compound used and improving production efficiency, for example, the molar ratio (molybdenum / gadolinium) may be 5 or less, 3 or less, or 2 or less. From the viewpoint of obtaining gadolinia particles with a smaller size, the molybdenum / gadolinium value is preferably less than 0.5.

[0081] As an example of the numerical range of the molar ratio (molybdenum / gadolinium), the value of molybdenum / gadolinium may be, for example, 0.01-5, 0.03-3, or 0.1-2.

[0082] As the amount of molybdenum used relative to gadolinium increases, there is a tendency for gadolinia particles having a larger particle size as shown in the above particle size distribution to be obtained.

[0083] Furthermore, the more molybdenum used relative to gadolinium, the more likely it is that gadolinia particles with less agglomeration will be obtained.

[0084] By using various compounds within the above ranges, the amount of molybdenum compound contained in the resulting gadolinia particles becomes more appropriate, and gadolinia particles with a controlled particle size can be easily obtained.

[0085] By using various compounds within the above ranges, the amount of molybdenum compound contained in the obtained gadolinia particles becomes more appropriate, and gadolinia particles with a controlled degree of aggregation can be easily obtained.

[0086] [Firing process] The sintering step is a step of sintering the mixture. The gadolinia particles according to the embodiment are obtained by sintering the mixture. As described above, this manufacturing method is called a flux method.

[0087] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).

[0088] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form idiomorphic crystals.

[0089] In the production of gadolinia particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. That is, when a gadolinium compound is fired in the presence of a molybdenum compound, gadolinium molybdate is first formed. At this time, as can be understood from the above explanation, the gadolinium molybdate grows gadolinia crystals at a temperature lower than the melting point of gadolinia. Then, for example, by evaporating the flux, gadolinium molybdate decomposes and crystals grow, thereby obtaining gadolinia particles. That is, the molybdenum compound functions as a flux, and gadolinia particles are produced via an intermediate called gadolinium molybdate.

[0090] By the above-mentioned flux method, gadolinia particles containing molybdenum can be produced.

[0091] The firing method is not particularly limited, and can be performed by a known, commonly used method. When the firing temperature exceeds 800°C, it is believed that the gadolinium compound and the molybdenum compound react to form gadolinium molybdate. Furthermore, when the firing temperature is 900°C or higher, it is believed that the gadolinium molybdate decomposes to form gadolinia particles. In addition, in gadolinia particles, it is believed that when gadolinium molybdate decomposes to form gadolinia and molybdenum oxide, the molybdenum compound is incorporated into the gadolinia particles.

[0092] The state of the gadolinium compound and the molybdenum compound during firing is not particularly limited, and they may be present in the same space so that the molybdenum compound can act on the gadolinium compound. Specifically, they may be simply mixed by mixing a powder of the molybdenum compound with a powder of the gadolinium compound, mechanically mixed using a grinder or the like, or mixed using a mortar or the like, or may be mixed in a dry or wet state.

[0093] The firing temperature is not particularly limited, and is appropriately determined in consideration of the particle size of the target gadolinia particles, the formation of molybdenum compounds in the gadolinia particles, the shape of the gadolinia particles, etc. The firing temperature may be 900° C. or higher, which is close to the decomposition temperature of gadolinium molybdate, 1000° C. or higher, or 1300° C. or higher.

[0094] The higher the sintering temperature, the more easily the particle shape is controlled and the larger the particle size of the gadolinia particles is obtained. From the viewpoint of efficiently producing such gadolinia particles, the sintering temperature is preferably 1100° C. or higher, more preferably 1200° C. or higher, and even more preferably 1300° C. or higher.

[0095] Generally, to control the shape of gadolinia particles obtained after sintering, it is necessary to sinter at high temperatures of over 2000°C, where the gadolinia reaction is likely to proceed. However, there are significant challenges to be overcome in terms of the burden on the sintering furnace and fuel costs in order to utilize this method industrially.

[0096] According to one embodiment of the present invention, even under conditions where the maximum sintering temperature for sintering a gadolinium compound is 1600° C. or lower, gadolinia particles can be formed efficiently at low cost.

[0097] Furthermore, according to the method for producing gadolinia particles of the embodiment, idiomorphous gadolinia particles can be formed regardless of the shape of the precursor even if the sintering temperature is 1600° C. or less, which is much lower than the melting point of gadolinia. From this viewpoint, the sintering temperature is preferably 1500° C. or less, more preferably 1400° C. or less, and even more preferably 1300° C. or less.

[0098] The range of the calcination temperature for calcining the gadolinium compound in the calcination step may be, for example, 900 to 1600°C, 1000 to 1500°C, 1100 to 1400°C, or 1200 to 1300°C.

[0099] From the viewpoint of production efficiency, the temperature rise rate may be 20 to 600° C. / h, 40 to 500° C. / h, or 80 to 400° C. / h.

[0100] Regarding the firing time, the time required for raising the temperature to a predetermined firing temperature is preferably within the range of 15 minutes to 10 hours. The holding time at the firing temperature can be 5 minutes or more, and is preferably within the range of 5 minutes to 1000 hours, and more preferably within the range of 1 to 100 hours. In order to efficiently form gadolinia particles, the firing temperature is preferably held for 2 hours or more, more preferably for 2 to 100 hours, and even more preferably for 2 to 48 hours.

[0101] As an example, by selecting conditions of a firing temperature of 900 to 1600° C. and a firing temperature holding time of 2 to 100 hours, gadolinia particles of the embodiment containing molybdenum can be easily obtained.

[0102] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.

[0103] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.

[0104] [Molybdenum removal process] The method for producing gadolinia particles according to this embodiment may further include, after the firing step, a molybdenum removal step of removing at least a portion of the molybdenum, as necessary.

[0105] As described above, since molybdenum sublimes during sintering, the molybdenum content present in the surface layer of the gadolinia particles can be controlled by controlling the sintering time, sintering temperature, etc., and the molybdenum content and state present in the layers other than the surface (inner layers) of the gadolinia particles can also be controlled.

[0106] Molybdenum may adhere to the surface of the gadolinia particles. As an alternative to the sublimation, the molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.

[0107] In this case, the molybdenum content in the gadolinia particles can be controlled by appropriately changing the concentrations and amounts of water, the aqueous ammonia solution, and the aqueous sodium hydroxide solution used, as well as the washing locations and washing times.

[0108] [Crushing process] In the fired product obtained through the firing step, the gadolinia particles may aggregate and may not satisfy the suitable particle size range for the intended application, so the gadolinia particles may be pulverized as necessary to satisfy the suitable particle size range.

[0109] The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.

[0110] [Classification process] The calcined product containing gadolinia particles obtained by the calcination step may be appropriately classified to adjust the range of particle sizes. "Classification" refers to an operation of classifying particles into groups according to their sizes.

[0111] The classification may be either a wet type or a dry type, but from the viewpoint of productivity, a dry type classification is preferred. Dry classification includes classification using a sieve as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag. From the viewpoint of classification accuracy, wind classification is preferred, and can be carried out using a classifier such as an air current classifier that utilizes the Coanda effect, a swirling air current classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.

[0112] The above-mentioned pulverization step and classification step can be carried out at any stage required. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, the average particle size of the obtained gadolinia particles can be adjusted.

[0113] The gadolinia particles of the embodiment, or the gadolinia particles obtained by the manufacturing method of the embodiment, are preferably those which are less agglomerated or are not agglomerated, as they are more likely to exhibit their inherent properties, are easier to handle, and have better dispersibility when dispersed in a dispersion medium for use.

[0114] In addition, according to the manufacturing method of gadolinia particles of the above embodiment, gadolinia particles with little or no agglomeration can be easily manufactured, and therefore, it has the excellent advantage that gadolinia particles having the desired excellent properties can be manufactured with high productivity without carrying out the above-mentioned crushing and classification processes. EXAMPLES

[0115] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0116] <Production of Gadolinia Particles> [Comparative Example 1] 3.0 g of commercially available gadolinium oxide (Gd2O3, manufactured by Aladdin (China)) was placed in a crucible and fired in a ceramic electric furnace at 1100°C for 24 hours. After cooling, the crucible was removed and 3.0 g of white powder was obtained.

[0117] [Comparative Example 2] The same procedure as in Comparative Example 1 was carried out except that the firing conditions were changed to 1300° C. for 24 hours, thereby obtaining 3.0 g of a white powder.

[0118] [Example 1] 3.0 g of gadolinium oxide Gd2O3 (manufactured by Aladdin (China)) and 0.15 g of molybdenum trioxide (manufactured by Chengdu Hongbo Industrial (China)) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible and fired in a ceramic electric furnace at 1100°C for 24 hours, and then fired at 1500°C for 24 hours. After cooling, the crucible was removed to obtain 3.15 g of white powder. Next, 3.15 g of the obtained white powder was suspended in 9 g of ion-exchanged water, and precipitated by spinning at 3000 rpm for 15 minutes in a centrifuge, and the supernatant was discarded. This operation was repeated six times to wash the white powder, and 3.07 g of white powder was obtained.

[0119] [Example 2] A powder of Example 2 was obtained in the same manner as in Example 1, except that the amount of molybdenum trioxide used in Example 1 was changed as shown in Table 1.

[0120] [Example 3] 3.0 g of gadolinium oxide Gd2O3 (manufactured by Aladdin (China)), 2.7 g of molybdenum trioxide (manufactured by Chengdu Hongbo Industrial (China)), 1.3 g of potassium carbonate (manufactured by Aladdin (China)), and 0.015 g of yttrium oxide (manufactured by Aladdin (China)) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible and fired in a ceramic electric furnace at 1300°C for 24 hours, and then fired at 1500°C for 24 hours. After cooling, the crucible was removed to obtain 5.355 g of white powder. Next, 5.355 g of the obtained white powder was suspended in 16 g of ion-exchanged water, and precipitated by spinning in a centrifuge at 3000 rpm for 15 minutes, and the supernatant was discarded. This operation was repeated six times to wash the white powder, and 32.97 g of white powder was obtained.

[0121] [Example 4] 3.0 g of gadolinium oxide Gd2O3 (manufactured by Aladdin (China)) and 3.6 g of sodium molybdate dihydrate (manufactured by Aladdin (China)) were mixed in a mortar to obtain a mixture. The mixture obtained was placed in a crucible and fired in a ceramic electric furnace at 1300°C for 24 hours. After cooling, the crucible was removed to obtain 6.6 g of white powder. Next, 6.55 g of the obtained white powder was suspended in 16 g of ion-exchanged water, and precipitated by spinning in a centrifuge at 3000 rpm for 15 minutes, and the supernatant was discarded. This operation was repeated six times to wash the white powder, obtaining 2.93 g of white powder.

[0122] <Evaluation> The washed powders obtained in Examples 1 to 4 and Comparative Examples 1 and 2 were used as sample powders and were evaluated as follows.

[0123] [Crystal structure analysis: XRD (X-ray diffraction) method] The sample powder was filled into a measurement sample holder with a depth of 0.5 mm, which was then set into a wide-angle X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2° / min, and scan range 10 to 70°.

[0124] [Particle size distribution measurement] The particle size distribution of the sample powder was measured in a dry state using a laser diffraction type dry particle size distribution analyzer (HELOS (H3355) & RODOS, manufactured by Japan Laser Co., Ltd.) under the conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar. The particle size at the point where the distribution curve of the volume cumulative percentage intersects with the horizontal axis at 10% from the small particle side was defined as D. 10 The particle diameter at the point where it intersects with the horizontal axis at 50% is D 50 The particle diameter at the point where the horizontal axis intersects with the 90% particle diameter from the small particle side is D 90 As such, we calculated the following:

[0125] [XRF (X-ray fluorescence) analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), approximately 70 mg of sample powder was placed on filter paper, covered with PP film, and XRF (X-ray fluorescence) analysis was performed under the following conditions. Measurement conditions EZ Scan Mode Measuring elements: F~U Measurement time: Standard Measurement diameter: 10mm Balance: None

[0126] The XRF analysis was performed to obtain the results of the Gd2O3 content (G1) relative to 100 mass% of the gadolinia particles, and the MoO3 content (M1) relative to 100 mass% of the gadolinia particles.

[0127] [XPS surface analysis] Surface elemental analysis of the sample powder was performed using an ULVAC-PHI QUANTERA SXM, with monochromated Al-Kα as the X-ray source, and X-ray photoelectron spectroscopy (XPS: X-ray photoelectron spectroscopy). The area was measured in a 1000 μm square area, and the average value of n=3 measurements was obtained in atom% for each element.

[0128] The gadolinium content and molybdenum content in the surface layer of the gadolinia particle obtained by XPS analysis were converted into oxides to determine the Gd2O3 content (G2) (mass%) relative to 100 mass% of the surface layer of the gadolinia particle and the MoO3 content (M2) (mass%) relative to 100 mass% of the surface layer of the gadolinia particle.

[0129] <Result> The values ​​obtained from the above evaluations are shown in Table 1. Note that "ND" is an abbreviation for "not detected," indicating that the substance was not detected.

[0130] [Table 1]

[0131] Scanning electron microscope (SEM) images of the powders of the above-mentioned Examples and Comparative Examples are shown in Figures 1 to 6. Granular or columnar particles were observed in each of the Examples and Comparative Examples.

[0132] The results of the XRD analysis are shown in Figure 7. Peaks (unmarked peaks) derived from gadolinium oxide (Gd2O3) were observed in the samples of each of the examples and comparative examples.

[0133] From the results of the SEM observation and XRD analysis described above, it was confirmed that the powders obtained in the examples and comparative examples were gadolinia particles containing gadolinium oxide (gadolinia).

[0134] The results of each example show that by firing a gadolinium compound in the presence of a molybdenum compound, it is possible to fire gadolinia oxide particles containing molybdenum even at relatively low firing temperatures of 1300°C and 1500°C.

[0135] From the SEM observation images of each gadolinia particle, the degree of particle aggregation was evaluated according to the following criteria. +: Particle aggregation is observed. -: No noticeable aggregation of particles is observed.

[0136] In the gadolinia particles of Comparative Examples 1 and 2, aggregation and fusion between particles was observed (degree of aggregation +), whereas no noticeable aggregation was observed in the gadolinia particles of Examples 2 to 4 (degree of aggregation -). In addition, in a comparison between Examples 1 and 2, aggregation and fusion between particles was observed in the gadolinia particles of Example 1, whereas no noticeable aggregation was observed in the gadolinia particles of Example 2.

[0137] These findings indicate that it is possible to produce gadolinia particles with low agglomeration tendency by calcining a gadolinium compound in the presence of a molybdenum compound, and further, that as the amount of molybdenum used increases, there is a tendency for particles with little or no agglomeration to be obtained.

[0138] Moreover, gadolinia particles having a large particle size were obtained from the gadolinia particles of Examples 3 and 4. This shows that gadolinia particles having a large particle size can be easily obtained by using an alkali metal salt of molybdenum oxoanion as a fluxing agent.

[0139] The values ​​of the above Gd2O3 content (G1), MoO3 content (M1), Gd2O3 content (G2), and MoO3 content (M2) are shown in Table 1.

[0140] From the results of the MoO3 content (M1) and the MoO3 content (M2), the gadolinia particles of Examples 1 to 4 contain molybdenum on the surface, and it is expected that various actions due to molybdenum, such as catalytic activity, will be exhibited.

[0141] Table 1 also shows the calculation results of the surface layer uneven distribution ratio (M2 / M1) of the MoO3 content (M2) to the MoO3 content (M1).

[0142] From the results of the surface layer uneven distribution ratio (M2 / M1), the molybdenum oxide content in the surface layer of the gadolinia particles determined by XPS surface analysis is higher than the molybdenum oxide content determined by XRF analysis in the gadolinia particles of Examples 1 and 4. This confirms that molybdenum is unevenly distributed on the surface of the gadolinia particles, and it is expected that various functions due to molybdenum will be effectively exerted.

[0143] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims.

Claims

1. Gadolinia particles containing molybdenum, The amount of Gd relative to 100 mass% of the gadolinia particles determined by XRF analysis of the gadolinia particles is 2 O 3 Content rate (G 1 ) is 70 to 98 mass %, and MoO relative to 100 mass % of the gadolinia grains is determined by XRF analysis of the gadolinia grains. 3 Content rate (M 1 % by mass of gadolinia particles.

2. The median diameter D of the gadolinia particles calculated by a laser diffraction / scattering method 50 The gadolinia particles according to claim 1, wherein the diameter of the gadolinia particles is 0.1 to 1000 μm.

3. The amount of Gd in the surface layer of the gadolinia particle is determined by XPS surface analysis of the gadolinia particle. 2 O 3 Content rate (G 2 ) is 10 to 98 mass %, and the MoO 3 Content rate (M 2 3. The gadolinia particles according to claim 1, wherein the content of ZnO is 2 to 40 mass %.

Citation Information

Patent Citations

  • Molybdate temperature-stable ultra-low dielectric constant microwave dielectric ceramic

    CN106986645A

  • Brittle material granules for a room-temperature vacuum granule spraying process and method for forming a coating layer using the same

    JP2014511260A